2019
DOI: 10.1002/jor.24183
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of a hierarchical electrospun scaffold for ovine anterior cruciate ligament replacement

Abstract: The anterior cruciate ligament (ACL) acts to stabilize the knee and prevent excessive motion of the tibia relative to the femur. Tears of the ACL are common and can result in pain and damage to surrounding tissues. Thus a torn ACL is often surgically replaced with an autograft or allograft material. Drawbacks to clinically available ACL grafts motivate the development of a tissue engineered ACL replacement. Our group has previously developed a polycaprolactone electrospun scaffold that mimics the hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Nevertheless, it has been demonstrated that electrospun PCL scaffolds are sufficiently mechanically robust to withstand in ex vivo models [54]. PLGA, PLLA, and PCL are among the most common synthetic biodegradable polymers (poly(α-hydroxy esters)) investigated for TE and have previously been used in certain FDA (US Food and Drug Administration) approved biomedical and drug-delivery devices [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that electrospun PCL scaffolds are sufficiently mechanically robust to withstand in ex vivo models [54]. PLGA, PLLA, and PCL are among the most common synthetic biodegradable polymers (poly(α-hydroxy esters)) investigated for TE and have previously been used in certain FDA (US Food and Drug Administration) approved biomedical and drug-delivery devices [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research is currently focused on the potential utility of electrospun scaffolds for clinical applications including the repair of diaphragm [1], bladder [2][3][4], and ligaments [5][6][7][8], as well as grafting procedures for bone [5,9], skin [10][11][12], and vascular [13,14] tissue. Electrospun scaffolds provide a 3-dimensional fibrous matrix with interconnecting pores, a feature that mimics the native extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…Other synthetic polymers used in electrospinning include poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) [22], poly (vinylidene fluoride) (PVD) [23], and poly (lactic acid) (PLA) [24]. While composite materials (e.g., PCL/collagen mixtures) are typically stronger than scaffolds composed solely of natural matrix molecules, the tensile strength of these composites rarely approaches the mechanical strength of tissues such as bone or tendon [8,12]. For many regenerative therapies, it is thought that the mechanical properties of an implanted scaffold should match that of the target tissue [25].…”
Section: Introductionmentioning
confidence: 99%
“…Poly (e-caprolactone) (PCL) is a semi-crystalline, hydrophobic, biodegradable polymer with satisfactory mechanical properties 41 and certificated by FDA. Compared with other polymers, PCL has more outstanding elastic property but lower tensile strength, making it a very good elastic biomaterial.…”
Section: Pclmentioning
confidence: 99%